Epidural Anesthesia and Arterial Maximal Flow Velocity of Free Flap in Patients Having Microvascular Lower Extremity Reconstruction: A Randomized Controlled Trial. Issue 2 (February 2022) - Park, Jun-Young; Suh, Hyunsuk Peter; Kwon, Jin Geun; Yu, Jihion; Lee, Joonho; Hwang, Jai-Hyun; Hong, Joon Pio; Kim, Young-Kug
Abstract : Background: One of the critical factors for free flap survival is to maintain adequate perfusion. The authors evaluated the effect of epidural anesthesia on arterial maximal flow velocity of the free flap in microvascular lower extremity reconstruction. Methods: This is a prospective randomized study where patients were allocated to receive either combined general-epidural anesthesia (epidural group, n = 26) or general anesthesia alone (control group, n = 26). After injecting epidural ropivacaine 10 ml in the epidural group, the effect on arterial maximal flow velocity of the free flap was analyzed using ultrasonography. The primary outcome measurement was the arterial maximal flow velocity 30 minutes after establishing the baseline. Intraoperative hemodynamics and postoperative outcomes such as postoperative pain, opioid requirements, surgical complications, intensive care unit admission, and hospital length of stay were also assessed. Results: The arterial maximal flow velocity 30 minutes after the baseline measurement was significantly higher in the epidural group (35.3 ± 13.9 cm/second versus 23.5 ± 8.4 cm/second; p = 0.001). The pain score at 1 hour postoperatively and opioid requirements at 1 and 6 hours postoperatively were significantly lower in the epidural group [3.0 (interquartile range, 2.0 to 5.0) versus 5.0 (interquartile range, 3.0 to 6.0), p = 0.019; 0.0 μg (interquartile range, 0.0 to 50.0 μg) versus 50.0 μg (interquartile range, 0.0 to 100.0 μg), p = 0.005; and 46.9 μg (interquartile range, 0.0 to 66.5 μg) versus 96.9 μg (interquartile range, 41.7 to 100.0 μg), p = 0.014, respectively]. There were no significant differences in intraoperative hemodynamics or other postoperative outcomes between the two groups. Conclusion: Epidural anesthesia increased the arterial maximal flow velocity of the free flap and decreased postoperative pain and opioid requirements in microvascular lower extremity reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, I.